Compressive strength at high temperature of recycled tire aggregate concretes - Santos, C.C. (2017)
This paper presents the results of an experimental research on the normal and high- temperature compressive strength of concretes with steel or textile fibres or rubber aggregates from recycled tires. The studied compositions included a reference (RC), two textile fibers (TF), two steel fibres (SF) and a rubber aggregates (RA) concrete. The specimens were tested in compression for different levels of temperature (20, 300, 500 and 700ºC). During the heating the specimens were subjected to a constant loading level of 0.5fcd. The results of this experimental program showed that steel and textile fibres are a good solution in the compressive behaviour of the concrete regarding to cracking control. The results for the rubber aggregate concrete revealed a loss on compressive strength with the increase of the rate of these aggregates in concrete.